SCOUT EXTRACURRICULAR CONSTRUCTION OF ELEMENTARY STUDENT DISCIPLINE CHARACTER BUILDING - Safitri, Iga Rahma; Busyairi, A. (Elementary School Teacher, 2020)
The purpose of this study was to describe the process o forming the disciplinary character of third grade students of SDNKarangasem 03 through scout extracurricular activities. This study used descriptive qualitative method. Data collectionuses observation, interview, questionnaire, and documentation techniques. Data analysis technique were carried out byvalidity testing using source triangulation, technique triangulation, and time triangulation and confirmability testing. Theresults of this study indicate that: (1) Formation of the character of discipline through scout extracurricular activities iscarried out at three stages, namely the initial stage which introduces conditions and activities, the central stage of thestudents begins to carry out activities, and the final stage is marked by students' awarness of disciplinary behavior; (2)There are five forms of scout extracurricular exercises such as the PBB (line rule), rigging, apple ceremonies, applause andsinging, and one-day camps that can build student discipline; (3) The process of constructing the character of disciplinethrough scout extracurricular activities has received acceptance and neglect responses. So that there are still spme childrenwho have not been disciplined.